2013
DOI: 10.1186/1743-422x-10-149
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with severe manifestations of 2009 pandemic influenza A (H1N1) infection in China: a case–control study

Abstract: BackgroundNo studies on the risk factors of 2009 pandemic influenza A (H1N1) in China have been reported. We aimed to investigate the risk factors for severe manifestations of 2009 pandemic H1N1 influenza in ChinaMethodsA case–control study with 343 severe hospitalized patients and 343 randomly selected mild controls was conducted. The diagnosis was established by assessment of clinical symptoms and confirmed by the real-time reverse-transcriptase-polymerase chain reaction assay. Severe or mild patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…According to the surveillance data of Jiangsu Provincial CDC, the overall obesity rate has increased from 9.5% to 14.6% from 2007 to 2013. It was reported that overweight could impair immunity against the influenza virus and was associated with an increased risk of severe infection . The increasing trend of overweight observed in the study has reminded public health experts of the importance of strengthening health education and of promoting precaution implementation in this high‐risk population.…”
Section: Discussionmentioning
confidence: 76%
“…According to the surveillance data of Jiangsu Provincial CDC, the overall obesity rate has increased from 9.5% to 14.6% from 2007 to 2013. It was reported that overweight could impair immunity against the influenza virus and was associated with an increased risk of severe infection . The increasing trend of overweight observed in the study has reminded public health experts of the importance of strengthening health education and of promoting precaution implementation in this high‐risk population.…”
Section: Discussionmentioning
confidence: 76%
“…Epidemiological evidence demonstrates that obesity increases the likelihood of severe influenza infection complications in humans (17, 37–40), and several mouse models have also confirmed this outcome (1015, 36). Obesity exacerbates lung inflammation and pathology, alters lung immune cell populations, impairs lung healing and in some cases increases viral titers during influenza infection in mice (1015, 36).…”
Section: Resultsmentioning
confidence: 94%
“…Following the emergence of the 2009 pH1N1 strain, obesity was reported to be an independent risk factor for greater pH1N1 (17, 37–40) and seasonal (4648) influenza infection severity. In this study, we provide an in-depth analysis of the immunologic and metabolic complications associated with obesity during infection with the 2009 pH1N1 influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, children have been at high‐risk for developing influenza‐related respiratory illnesses, especially during the fall and winter seasons. Several studies have identified risk factors associated with the severity and morbidity of influenza infections, including age, race/ethnicity, chronic diseases, access to health care, and obesity …”
Section: Introductionmentioning
confidence: 99%